PEMBELAJARAN BAHASA ARAB ANAK-ANAK BERBASIS SITUS DARING (PENDEKATAN MAHARAH LUGHAWIYYAH) - Ahmad Zaki Annafiri (El-Tsaqafah : Jurnal Jurusan PBA, 2022)
The era of technological disruption has now touched various sectors, one of which is the education sector, especially Arabic language education. Arabic teachers need great attention so that students can adapt to the rapid changes in technology. However, most students have not been able to take advantage of access to technology optimally. This study aims to analyze Arabic learning online sites from the four aspects of maharah lughawiyyah, advantages and disadvantages, and aspects of financing. The study used a qualitative descriptive approach with content analysis. The primary sources of this research are 8 recommended online Arabic learning sites. The secondary sources are books, journals, and other references related to maharah lughah arabiyyah. This research shows, from the aspect of maharah lughawiyah, the only site that trains all aspects is nahwawanahil.com, while there are no other sites that provide specific aspects of maharah kalam training. For the other three maharah, 6 sites provide it in full. Only belarabyapps.com does not cover the three maharah, but only trains the maharah qiraah and the book. From the aspect of financing, only the sites arabiyah.net and belarabyapps.com provide it for free, while apart from these two, it requires a registration and financing system that needs adult assistance. However, the eight sites are worthy of being used as references for learning Arabic, especially for the online site category.